A Primer for Critics: Callaghan's A Fine and Private Place - Freiburger, John (My University, 1980)
After a half-century of writing, Morley Callaghan has earned a place in Canadian literature. The difficulty in this is that Callaghan wants no such place.
To locate Callaghan in our literary development, Canadian critics have attached labels, sought out resemblances and dependences, applied extrinsic analytical tools such as Jungian psychological theory, and finally, they have treated his work with special consideration because he is Canadian. In short, they have reduced his work to a sterile series of commonalities, and have ignored its individuality and mystery.
A Fine and Private Place is, in part, a reaction to such critics. It shows the shallowness of critic J.C. Hilton, and traces the right education as a critic of Al Delaney as he moves from his dependence on scholarship to a trust in his heart's reaction to Eugene Shore's writing. In particular, the novel shows that its realism can be verified by a Jungian framework, and yet that the framework does not encapsulate Callaghan's creativity. As a fine tale, it has a charm and intimacy which critical tools cannot dissect.
The novel alludes to three other Callaghan works: The Loved and the Lost, More Joy in Heaven, and Such Is My Beloved. In this context, A Fine and Private Place reveals its place in an evolving treatment of the rivalry between criminal-saints and their repressive societies, with the value of the individual as the prize.
Callaghan's works must not be trapped in a literary mosaic: they must be accepted by the reader in private on their own merits. A Fine and Private Place is both a request for such treatment and a critical tool to assist in the task.
Keywords: English; English Language and Literature; English Language and Literature